Social Injustice and Discrimination in Lessing’s Going Home - Burhan Kakakhan , Mohammed (Journal of College of Education, 2020)
Having a deep, emotional, memorial with a country where everyone’s main concern was politics all the time, Doris Lessing is seemingly politically-minded. Going Home, which is an account of her return to Rhodesia (Zimbabwe), shows a clear view of Lessing’s declared opposition to illiberal white rule. This paper explores the social structure of Rhodesia at that time. Southern Rhodesia structure was based on oppression, an oppression based purely on race. Once Lessing returns to her native land she again observes, reports the bloody-minded whites to accept the black as humans. Lessing claims that due to her attitude to abolish the white rules in Africa she was declared to be a Prohibited Immigrant. Thus, Going Home can be read as bifocally both as an experience of a nation with persecution and her own experience with exile.